The Impact of Working Capital and Macroeconomic Variables on the Profitability of Listed Industrial Firms in South Africa - Emmanuel, Mutambara Tatenda; Phocenah, Nyatanga; Kerry, McCullough (International Journal of Economics and Financial Issues, 2023)
This study examines the impact of working capital management policies (WCMP) and macroeconomic variables on the profitability of 83 industrial firms listed on the JSE over the period 2010-2020. The system Generalized Method of Moments (GMM) approach was employed in regression analysis to deal with the existence of endogeneity. Results establish that working capital investment policy (WCIP) is significantly and negatively related to firm profitability. A significant and positive relationship was found between working capital financing policy (WCFP) and firm profitability. Contrary to our expectations, interest rates demonstrated significant and positive relations with return on assets(ROA). Exchange rates and inflation rates proved to impact firm profitability significantly and negatively, which resulted in the study recommending JSE-listed industrial firms to pay special attention to the external environment. Economic growth influenced firm profitability positively and significantly, which aligned with the idea that GDP growth increases the average consumers' income per capita, increasing the goods and services consumed, enhancing profitability.